KORELASI LAMA HEMODIALISA DENGAN FUNGSI KOGNITIF - Wahyuni, Aria; Kartika, Imelda Rahmayunia; Asrul, Imelda Firdausy; Gusti, Eka (Universitas Fort De Kock Bukittinggi, 2019)
Hemodialysis can remove uremic toxins for cognitive process improvement in hemodialysis patients. This study aims to determine the long-standing relationship of hemodialysis to the cognitive function of patients with chronic renal failure. This type of research is descriptive analytic with a cross sectional study design. The population in this study were patients who underwent hemodialysis with the sampling technique used was total sampling totaling 83 respondents. The study was conducted in May - June 2018 in the hemodialysis unit. The instrument used to measure cognitive function is MMSE (Mini Mental State Exam). Data analysis used was univariate analysis and bivariate analysis using correlation test. The results showed that the duration of hemodialysis was the lowest 1 week and the highest 96 months with a mean duration of 21 months hemodialysis, the lowest cognitive function score 7 and the highest 30 scores with the average cognitive function was 18. Relationship analysis showed no long association of hemodialysis with function cognitive (p Value = 0.375; r = 0.099). This study provides recommendations for further research related to factors that influence cognitive impairment in hemodialysis patients and it is expected that nurses improve the quality of cognitive function nursing care in hemodialysis patients at risk of cognitive impairment.Keywords: Cognitive Function, Hemodialysis